2010
DOI: 10.1063/1.3490249
|View full text |Cite
|
Sign up to set email alerts
|

Strong ferroelectric domain-wall pinning in BiFeO3 ceramics

Abstract: We have studied the polarization-electric-field hysteresis, the dielectric permittivity dispersion, the piezoelectric properties, the electric-field-induced strain, and the interrelations between these properties for bismuth ferrite (BiFeO3) ceramics. The results indicate that the domain-wall movement in BiFeO3 is strongly inhibited by charged defects, most probably acceptor-oxygen-vacancy defect pairs. The domain-wall mobility can be considerably increased by preventing the defects from migrating into their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
230
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(254 citation statements)
references
References 34 publications
17
230
2
Order By: Relevance
“…10 In spite of the extensive research on BiFeO 3 and its chemical modifications, the knowledge of the piezoelectric response of pure BiFeO 3 ceramics is rather poor and usually only values of d 33 are reported, which range from 4 to 60 pm/V. [11][12][13][14] The reason for the large spread in the values is probably a combination of high electrical conductivity and high coercive field (50-85 kV/cm), which are strongly processing sensitive, 11,[15][16][17][18] and difficulties in processing the ferrite. [19][20][21] The problem of the high electrical conductivity, which prevents application of high electric fields to BiFeO 3 , is often overcome by measuring the electromechanical response only locally using piezoforce microscopy (PFM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In spite of the extensive research on BiFeO 3 and its chemical modifications, the knowledge of the piezoelectric response of pure BiFeO 3 ceramics is rather poor and usually only values of d 33 are reported, which range from 4 to 60 pm/V. [11][12][13][14] The reason for the large spread in the values is probably a combination of high electrical conductivity and high coercive field (50-85 kV/cm), which are strongly processing sensitive, 11,[15][16][17][18] and difficulties in processing the ferrite. [19][20][21] The problem of the high electrical conductivity, which prevents application of high electric fields to BiFeO 3 , is often overcome by measuring the electromechanical response only locally using piezoforce microscopy (PFM).…”
Section: Introductionmentioning
confidence: 99%
“…9,12,22 Using a mechanochemically assisted synthesis, we have recently succeeded to prepare BiFeO 3 ceramics with sufficiently low DC conductivity to withstand large electric fields, i.e., up to 180 kV/cm. 15 As a result of electric-field switching of domains, a large strain, comparable to 4 that achievable in Pb-based ferroelectric ceramics with MPB compositions, such as Pb(Zr,Ti)O 3 (PZT) and Pb(Mg,Nb)O 3 -PbTiO 3 (PMN-PT), was measured in these BiFeO 3 ceramics. 23 Those results suggested that the weak-field electromechanical response of the ferrite may also involve a considerable contribution of non-180° domain-wall movement.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of double hysteresis loop has been found in various materials, such as Pb(Zr,Ti)O 3 [18], BiFeO 3 [19], and BaTiO 3 [20]. In these system, some types of inhomogeneity, structural disorder, and structural defects with local polarity are present in these materials, leading to the domain walls being strongly pinned by defects [18,19]. In addition, pinched hysteresis loops exhibit a small polarization for a zero electric field.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly believed that double hysteresis loops above the Curie temperature should be considered pinched hysteresis loops because there exist a region with some polar regions embedded in the non-polar matrix. This kind of double hysteresis loop has been found in various materials, such as Pb(Zr,Ti)O 3 [18], BiFeO 3 [19], and BaTiO 3 [20]. In these system, some types of inhomogeneity, structural disorder, and structural defects with local polarity are present in these materials, leading to the domain walls being strongly pinned by defects [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It was later shown that charged defects like oxygen vacancies impede the motion of domain walls, causing non-saturated ferroelectric hysteresis loops. 23 Quenching from above the ferroelectric transition temperature causes Figure 3 Crystal structure of a perovskite ABO 3 with a tetragonal ferroelectric distortion. randomization of the defects and yields saturated loops with respectable polarization values (B20 mC cm À2 ), but still not comparable to those achieved in thin films and single crystals.…”
Section: Bifeomentioning
confidence: 99%